Insect communities in big sagebrush habitat are altered by wildfire and post‐fire restoration seeding. Issue 3 (8th November 2018) - Rohde, Ashley T.; Pilliod, David S.; Novak, Stephen J.
Abstract: Natural resource managers sow grass, forb, and shrub seeds across millions of hectares of public lands in the western United States to restore sagebrush‐steppe ecosystems burned by wildfire. The effects of post‐fire vegetation treatments on insect communities in these ecosystems have not been investigated. We conducted the first investigation of insect community responses to post‐fire seeding on public rangelands by comparing the composition of insect communities at burned‐and‐seeded (treatment) and burned‐and‐unseeded (control) sagebrush‐steppe ecological sites in southwestern Idaho. Insect communities in burned areas were compared to unburned (reference) areas. Insect communities in burned plots did not resemble those in reference plots. Treatment plots had greater inter‐annual variability in insect community composition than control or reference plots, suggesting that communities may be less stable in seeded areas. The vegetation composition of the landscape surrounding plots influenced mobile species. Wildfire and post‐fire seeding may have lasting effects on insect communities in sagebrush‐steppe ecosystems. Wildfires decrease shrub cover. Post‐fire seeding increases perennial bunchgrasses and, where successful, reduces non‐native annual grasses. These habitat changes influence insect community composition. Future studies are needed to expand the inference of this study.